Spatial encoding in mountain chickadees: features overshadow geometry. - Gray, E; Bloomfield, L; Ferrey, A; Spetch, M; Sturdy, C (2005)
Encoding the global geometric shape of an enclosed environment is a principal means of orientation in human and non-human animals. Animals spontaneously encode the geometry of an enclosure even when featural information is available. Although features can be used, they typically do not overshadow geometry. However, all previously tested organisms have been reared in human-made environments with salient geometrical cues. Here, we show that wild-caught mountain chickadees (Poecile gambeli) do not spontaneously encode the geometry of an enclosure when salient features are present near the goal. However, chickadees trained without salient features encode geometric information, but this encoding is overshadowed by features.